Characterisation of Field Established Tissue Culture Derived Black Pepper (Piper nigrum L.) Plants using Morphological, Cytological and molecular Markets - Sujatha R (Department of Plant Breeding and Genetics, College of Horticulture, 2001)
Universally acclaimed as the ' King of Spices', black pepper (Piper nigrum L.) enjoys a unique position as a commercial crop of historical importance and assumes great economic importance to several nations of the world. Efforts to evolve high yielding types of black pepper through selection as well as hybridisation started as early as in 1953 (Nambiar et al., 1978) and by now, about ten improved varieties were evolved and released. In order to meet the insatiable demand from farmers for the planting materials of high yielding pepper varieties, mass multiplication protocol through micro-propagation has been standardised (Joseph et al., 1996). Babu (2000) tested the fidelity of TC plantlets of black pepper during the hardening stage using RAPD assay. A thorough evaluation and characterisation of these 'I'C plants in relation to their performance in the field is a prerequisite to establish their heritage and usefulness. In this background, the present study was taken up with the main objectives of establishing the genetic identity of TC derived black pepper plants in field; testing the intra-group, inter-clonal and inter- varietal polymorphism and obtaining a thorough and fool proof finger print of the TC plants using a combination of molecular marker techniques and conventional markers. Each of the experimental vines was characterised using morphological traits (biometric as well as qualitative) based on the descriptor formulated by NBPGR. The cytological studies ruled out any variation caused by a change in the chromosome number, which is possible in in vitro cultured plants. The somatic chromosome number was found uniform in all the vines with 2n = 52, which is characteristic of the species. The molecular markers provided a more specific identity for each of the experimental vines. The